Rufinamide-Loaded Chitosan Nanoparticles in Xyloglucan-Based Thermoresponsive In Situ Gel for Direct Nose to Brain Delivery - Dalvi, Avantika; Ravi, Punna Rao; Uppuluri, Chandra Teja (Frontiers in Pharmacology, 2021)
In 2004, the US FDA approved Rufinamide, an anti-epileptic drug under the brand name Banzel®. 2 In 2015, Banzel® received approval for its use in pediatric patients (ages 1-4 years). Rufinamide 3 shows low oral bioavailability due to a low dissolution rate resulting in less drug reaching the 4 brain. This has led to high dose and dosing frequency of Rufinamide. 5 In this work, using the principle of Design of Experiments (DoE), we have formulated Rufinamide-6 loaded chitosan nanoparticles and suspended them in a solution of a thermoresponsive polymer – 7 tamarind seed xyloglucan to form a nasal in-situ gel for direct nose to brain delivery of Rufinamide. 8 The nanoparticles were characterized for particle size, entrapment efficiency, zeta potential, and 9 physical stability. The in-situ gel formulations were characterized for rheological properties, 10 stability, and in vivo plasma and brain pharmacokinetics. Pharmacokinetic parameters were 11 computed for aqueous suspension of nanoparticles and in situ gelling formulation for nanoparticles 12 and compared with the pharmacokinetic parameters of an aqueous suspension of plain Rufinamide. 13 The percent direct transport efficiency (% DTE) and direct transport percent (%DTP) values were 14 calculated for all the formulations. 15 The optimized nanoparticle formulation showed a size of 180±1.5 nm, the zeta potential of 16 38.3±1.5 mV, entrapment efficiency of 75±2.0 %, and drug loading of 11±0.3 %. The in-situ 17 gelling formulations of nanoparticles showed a solution to the gel transition temperature of 32 °C. 18 The %DTE values for aqueous suspension of nanoparticles and in situ gelling formulation for 19 nanoparticles were 988.5 and 1177.3 and the %DTP values were 86.06 and 91.5, respectively.